2023
DOI: 10.3390/brainsci13050828
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Lumbosacral Nerve Roots in Patients with Type 2 Diabetic Peripheral Neuropathy Using Diffusion Tensor Imaging

Abstract: Background: Diffusion tensor imaging (DTI) has found clinical applications in the evaluation of the central nervous system and has been extensively used to image peripheral neuropathy. However, few studies have focused on lumbosacral nerve root fiber damage in diabetic peripheral neuropathy (DPN). The aim of the study was to evaluate whether DTI of the lumbosacral nerve roots can be used to detect DPN. Methods: Thirty-two type 2 diabetic patients with DPN and thirty healthy controls (HCs) were investigated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
(74 reference statements)
0
1
0
Order By: Relevance
“…DTI parameters, such FA and ADC, have been found effective in detecting nerve abnormalities in patients with type 2 diabetes and peripheral neuropathy. Decreased FA and increased ADC values are observed in the lumbosacral nerve roots of patients with DPN compared to healthy controls (33,34). A study reported that acupoint injection of mecobalamin at Zusanli (ST36) could treat DPN and repair damaged nerves, as indicated by increased FA and decreased ADC in DTI (35).…”
Section: Introductionmentioning
confidence: 99%
“…DTI parameters, such FA and ADC, have been found effective in detecting nerve abnormalities in patients with type 2 diabetes and peripheral neuropathy. Decreased FA and increased ADC values are observed in the lumbosacral nerve roots of patients with DPN compared to healthy controls (33,34). A study reported that acupoint injection of mecobalamin at Zusanli (ST36) could treat DPN and repair damaged nerves, as indicated by increased FA and decreased ADC in DTI (35).…”
Section: Introductionmentioning
confidence: 99%